DESAIN PRIMER IN SILICO UNTUK AMPLIFIKASI GEN gyrA PADA Escherichia coli DENGAN POLYMERASE CHAIN REACTION (PCR) - Munakarim, Arbela Hafsah; Qurrohman, Muhammad Taufiq Qurrohman; Dewangga, Vector Stephen (Universitas Islam Indonesia, 2025)
Background: The gyrA gene is an important genetic marker associated with fluoroquinolone resistance in Escherichia coli. Accurate primer design is crucial for enabling the successful amplification of this gene using the polymerase chain reaction (PCR).Objective: This study aims to evaluate the effectiveness of the designed primer pair in amplifying the gyrA gene in ciprofloxacin-resistant E. coli isolates.Method: DNA from E. coli isolates was extracted using the Presto™ Mini Bacteria Kit, followed by qualitative and quantitative analysis using UV-Vis spectrophotometry. Primer design was performed using databases and tools from NCBI, OligoEvaluator, and NetPrimer. PCR amplification was optimized at an annealing temperature of 59 °C, and results were visualized by agarose gel electrophoresis using a GelDoc system.Results: The qualitative test showed a clear DNA band, while the DNA purity ratio was 1.5, showing mild protein contamination. PCR amplification successfully produced a distinct DNA band at 221 bp, confirming that the primer pair was specific and effective.Conclusion: The primer pair (Forward: 5′-ACTGTGAAGAAAACCGTCCT-3′; Reverse: 5′-CCTAAACGAATACCGCGAAC-3′) is effective for amplifying the gyrA gene in E. coli and is suitable for further molecular detection applications.